The Creation of Dynamic Visual Objects as a Factor for Optimizing Advertisements in E-Commerce - Sysoiev, Volodymyr; Kuchina, Svitlana; Kitchenko, Olena; Romanchik, Tatiana; Kuchin, Alexandr (Jurnal The Messenger, 2022)
Introduction: The Covid-19 pandemic has boosted the development of online retail and has created an urgent need to transform digital marketing tools. The purpose of the study is to find ways to optimize advertising in Google and Facebook, which are the superior digital advertising platforms as their top digital advertising platforms in terms of both usage and performance.Methods: An experiment conducted as part of the study showed that the use of the dynamic optimization tool allows you to enrich existing feed data with additional 1st and 3rd party data and automatically compile visuals with additional information obtained from the feed and additional graphical overlays. The proposed method was tested on Facebook and Google with an analysis of click through rate, conversion rate and conversion cost indicators.Findings: The research results showed that the use of the dynamic optimization tool improves the effectiveness of online advertising, all the studied indicators has improved on both platforms. The results obtained complement to the few literature sources devoted to creating enriched feeds on various internet companies, so the work is of significant interest for marketers and business owners who work in the field of e-commerce. Originality: It has been established that in order to increase the conversion rates of ad campaigns and improve the quality of communication with the audience, a deeper study of the behavioral characteristics of visitors of internet resources, as well as high-quality visual content of the ads, are required.